Examination of primary school teachers’ attitudes and views towards multicultural education - Erkanlı, Aysel; Batman, Kemal Akkan; Kaptanoğlu, Can (Frontiers in Education, 2024)
Just like in many countries around the world, there is a multicultural society in Northern Cyprus. As migrations to the island continue to increase, the phenomenon of multiculturalism has begun to be discussed in the education system. This research was conducted with the aim of determining the attitudes and views of primary school teachers in Northern Cyprus towards multicultural education. Mixed methods strategy was used in this research. In the research, the concurrent triangulation strategy from mixed methods strategies was usedIn the study, explanatory sequential design and mixed methods approach were used in the research. Data collection tools included the Teacher Multicultural Education Attitude Scale developed by Ponterotto, Baluch, Greig, and Rivera (1998) and adapted into Turkish by Yazici, Basol, and Toprak (2009), as well as an interview form developed by the researchers. In the quantitative part of the research, the Teacher Multiculturalism Attitude Scale was applied to 111 randomly selected teachers. According to the survey results, no significant difference was detected depending on the variables of gender, nationality, professional seniority, branch, graduation degree and graduated school. However, significant differences were identified in the multiculturalism scores age and based on the region where the teachers were employed. In the qualitative part of the research, interviews were conducted with 12 participant teachers. According to the qualitative findings, teachers perceived multiculturalism as diversity in terms of nationality, ethnic background, language, and religion. Further, teachers indicated that education in Northern Cyprus does not cater to a multicultural structure, leading to various problems experienced by students and parents, primarily related to communication. The teachers attributed this situation to the unpreparedness of the Ministry of Education (MEB) and the reluctance to change education policies due to an exclusive society. Subsequently, teachers expressed that they did not consider themselves competent in multicultural education and expressed a willingness to participate in in-service training programs if provided.